America Already Led, Tested and Proved Many of the Solutions: One Day They Are Inevitable - Philip Alpers (Washington University Journal of Law & Policy, 2019)
This article argues that historical lessons in gun control point the way to potential improvements in U.S. gun control in the future. The article begins by examining Australia’s response to the Port Arthur massacre in 1996, where the country acted quickly to ban certain weapons under the leadership of a conservative prime minister. Having had eleven mass shootings in the decade before the ban, Australia had zero in the two decades after. The article notes that similar programs were proposed in America by President Franklin Roosevelt, among others, and argues that they are likely to be enacted within the next generation or two.
Keywords: gun control; Australia; gun violence; Port Arthur massacre; ban